2015
DOI: 10.1044/2015_lshss-14-0057
|View full text |Cite
|
Sign up to set email alerts
|

Procedures for Obtaining and Analyzing Writing Samples of School-Age Children and Adolescents

Abstract: SLPs can readily implement many techniques for obtaining and analyzing writing samples. The information in this article provides SLPs with recommendations for the use of writing samples and may help increase SLPs' confidence regarding written language assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In the present work, findings suggest that written language productivity (Price & Jackson, 2015) and dialectneutral ungrammatical forms are reflective of general underlying language ability. Production of longer written narratives suggests more fluent and less effortful writing, which in turn reflects stronger underlying expressive language skills.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In the present work, findings suggest that written language productivity (Price & Jackson, 2015) and dialectneutral ungrammatical forms are reflective of general underlying language ability. Production of longer written narratives suggests more fluent and less effortful writing, which in turn reflects stronger underlying expressive language skills.…”
Section: Discussionsupporting
confidence: 53%
“…Undergraduate students enrolled in the speech-language pathology major typed the written samples into electronic transcript files. Transcripts were then formatted using Systematic Analysis of Language Transcripts (SALT) software and conventions ( Miller & Iglesias, 2017 ), and segmented into t-units by undergraduate research assistants following conventions of segmenting writing samples ( Price & Jackson, 2015 ). All research assistants received training in SALT transcription and segmentation and demonstrated at least 90% reliability with the first author on word-by-word transcription, t-unit segmentation, and SALT conventions on practice transcripts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzing the microstructure of language samples, MLU and NDW are a commonly used index of language maturity and are thought to reflect lexical diversity (Miller, Andriacchi, & Nockerts, 2015). NDW is reportedly the most commonly used language sample measures to assess lexical diversity (J. R. Price, Jackson, Nippold, & Ward-Lonergan, 2015) and is utilized in child language research as an index of language maturity to differentiate children with and without language learning disorders (Thordardottir & Namazi, 2007), to monitor oral language proficiency in DLLs (Jacobson & Walden, 2013), and to monitor progress in the language development of children with language disorders (Ertmer, Strong, & Sadagopan, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…NDW has also been identified as a measure to monitor oral language proficiency in dual language learners (Jacobson & Walden, 2013) and to progress monitor language development in children after cochlear implantation (Ertmer, Strong, & Sadagopan, 2003). When analyzing written language samples, NDW is reportedly the most common measure used in assessing lexical diversity (Price & Jackson, 2015); however, less research has been conducted on its use in written samples.…”
mentioning
confidence: 99%